Impaired nephrogenesis in neonatal rats with oxygen‐induced retinopathy. Issue 6 (24th April 2017) - Nakagawa, Mayu; Nishizaki, Naoto; Endo, Amane; Someya, Tomonosuke; Saito, Yuta; Mizutani, Akira; Hara, Taichi; Murano, Yayoi; Sakuraya, Koji; Hara, Satoshi; Umino, Daisuke; Hirano, Daishi; et al.
Abstract: Background: Preterm neonates are born while nephrogenesis is ongoing, and are commonly exposed to factors in a hyperoxic environment that can impair renal development. Oxidative stress has also been implicated in the development of retinopathy of prematurity (ROP). The rat model of oxygen‐induced retinopathy (OIR) is the most clinically relevant model of ROP because its biologic features closely resemble those of ROP in preterm infants. We investigated impaired renal development in a rat model of OIR. Methods: Newborn Sprague–Dawley rats were maintained in either a normoxic (room air, 21% O2 ; control group) or a controlled hyperoxic (80% O2 ; OIR group) environment from birth to postnatal day (P) 12. All pups were then raised in room air from P12 to P19. Results: The hyperoxic environment led to significantly higher urinary excretion of 8‐hydroxy‐2′‐deoxyguanosine, a marker of oxidative DNA damage, and a reduction in nephrogenic zone width at P5 in OIR pups. Additionally, glomerular count was significantly reduced by 20% in the OIR group, and avascular and neovascular changes in the retina were observed only in the OIR group at P19. Messenger RNA levels of vascular endothelial growth factor‐A (VEGF‐A) and platelet‐derived growth factor‐β, essential angiogenic cytokines for glomerulogenesis, in the renal cortex were significantly lower at P5 and significantly higher at P19 in the OIR group compared with controls. Conclusion: Renal impairment was caused by exposure to a hyperoxic environment during nephrogenesis, and the pathology of the impaired nephrogenesis in this OIR model reflects the characteristics of ROP observed in preterm infants.